Keberlanjutan Mata Pencaharian di Lahan Gambut Provinsi Kalimantan Tengah, Indonesia: Analisis Opsi Pemanfaatan Sumber Daya Lahan Gambut di Desa Buntoi, Desa Basarang Jaya, Desa Sabangau Permai, dan Desa Karang Sari - Nasir, Darmae (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Peatland resources in Central Kalimantan have long been utilized by the local communities for various activities such as agriculture, gathering, hunting, and timber extraction. The successful exploitation of peatland prompted the Indonesian Government to develop the region through a transmigration program, providing new settlements for people from Java, Madura, and Bali islands who were initially have no experience cultivating peatland. Land suitability issues have resulted in surprises, stress, and a decline in livelihoods among transmigrant populations, particularly concerning the failures in agriculture, especially in cultivating rice, the primary staple food for Indonesians. This research aims to examine the sustainability of livelihoods, determine the conservation aspirations and perceptions of stakeholders, and present alternative land use scenarios. Four villages were selected as samples, including a local village (Buntoi), two migrant villages in peatlands (Basarang Jaya and Sabangau Permai), and one migrant village outside the peatland area (Karang Sari). Data were obtained through interviews and group discussions involving farmers, entrepreneurs, and government officials. The research findings indicate that agriculture on peatlands can be developed through three stages of evolution: the early period, transition and recovery period, and stability or failure period. The stability period may take a long time, up to 20 years, as experienced by farmers in Basarang Jaya. This study provides insights into the sustainability of livelihoods and land use aspirations in Central Kalimantan. Keywords: Livelihood, peatlands, sustainable, utiliztion